Knowledge and practices of decontamination during root canal treatment by dentists in Jeddah - Maysoon Haji Albahiti (Saudi Dental Journal)
Background: The periapical area is healed through disinfection of root canal system and reduction of microbial infection after root canal. Purpose: To assess the knowledge of dental practitioners about decontamination during root canal treatment and the techniques used in the government and private sectors of Jeddah, Saudi Arabia. Methods: 103 dental practitioners and interns from private and governmental sectors performing root canal treatment were included. To extract information, a questionnaire assessing knowledge and preferred techniques used in decontamination during root canals treatment was distributed. The association of variables was investigated using chi-square tests. Results: The findings reflected that 82.5% of subjects used rubber dam for isolation with significantly more practitioner in the governmental (95.2%) as compared to the private sector (27.8%). Chelating agents were used by 13.3% of the practitioners in government sector and 1% practitioners in private sector (1%). The most commonly used irrigant was sodium hypochlorite. Calcium hydroxide was used more frequently in the governmental sector (29.8%) than in the private sector (11.8%), as intracanal medicament. Mechanical irrigation devices were used by 2.4% of practitioners in the governmental sector only. Conclusions: There is a significant difference in practicing root canal disinfection techniques among dentists in governmental and private sectors but no difference in degree of knowledge.